(3JbjjO CHj GdMSjf GdRhjdi Ydi GdeOhfIs - (3CHh GdMSf Ydj Hf eMeO Hf YHO GdMb GdRhjdj GdeGdcj GdUZjQ,J (B719 (3g` s
(3ChdgG (B:s
(3cJGH GdML GdChd s
(3BNQgG (B:s
(3Je cJGH GdfcGM GdKGdK HMeO Gddg hYhfg hJhajbg s
(3GdeOhfI ai aQhY GdeGdcjI dCHi GdbGSe (B- (3J (B191 (3g`s
(3GdfSNI ebJUQI Ydi GdLRA GdKGfi ef GdcJGHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdeGdcjs